The Comparative Turn in Climate Change Adaptation and Food Security Governance Research - Purdon, Mark (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Central to this working paper is the notion that the concepts and methods of comparative politics can shine light on political factors important for catalysing positive change on the governance climate change adaptation and food security in the developing world. I first introduce comparative politics, including discussion of epistemological and methodological issues, before reviewing three salient groups of political and economic factors identified by the comparative politics literature—institutions, ideas and interests—as well as highlighting the important relationship between international and domestic politics. Such organization is important because it draws attention to important gaps in the existing climate change adaptation and food security literature, which tends towards a form of normative analysis that privileges institutions. The paper closes by making five recommendations for CCAFS future research: the need (i) to identify new dimensions for institutional research, (ii) to conduct governance research beyond institutions, (iii) to embrace more rigorous comparative methods, (iv) to address the “dependent variable” problem in climate change adaptation research and (v) to come to grips with “good enough” climate governance.